Study to assess the acceptability and feasibility of cervical cancer screening using visual inspection with acetic acid and treatment of precancerous lesions using cryotherapy in low resource settings - Sheth, Tosha M.; Maitra, Nandita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Objective of current study was to assess the acceptability and feasibility of cervical cancer screening using VIA, and treatment of precancerous lesions using cryotherapy in low resource settings Methods: 526 women from three primary health centers of Shinor taluka (population based approach) and 250 women of Medical College, Vadodara (facility based approach) were sensitized and screened for cervical cancer. Visual Inspection with Acetic acid (VIA) was performed as the screening test. In the population based approach, VIA positive women were referred to a Community Health Centre (CHC) for colposcopy and biopsy. Ablative treatment in the form of cryotherapy was offered. Patients requiring higher forms of treatment were referred to medical college, Vadodara. In the facility based approach, VIA positive women underwent colposcopy. Guided biopsy was performed in those with positive lesions on colposcopy. Cryotherapy was offered in the same sitting. Those not suitable for cryotherapy were offered loop electrosurgical excision procedure. Women found to have invasive cancer were offered definitive management. Results: VIA positivity rate was 18.8% in the population based approach and 27.2% in the facility based approach.58.8% women in the population based approach and 77.77% women in the facility based approach were treated with cryotherapy on the same day as screening and none reported any severe side effects. Dropout rate in the community approach was 32.32% whereas in the facility it was 0.4%. Conclusions: VIA and cryotherapy procedures were well tolerated by all screened women. This project has shown that the “screen and treat” approach can be successfully implemented in the existing health setup.